INDIA DECISION-MAKING FACTORS IN SUPPORT OF ISRAEL IN THE WAR AGAINST HAMAS (PALESTINE) IN 2023 - Firdausi, Rayhan Fasya (Jurnal Paradigma, 2024)
The Israeli-Palestinian war erupted again after Hamas attacked Israel in 2023. This war drew responses from various parties. Among the many Asian countries that provide support to Palestine, India is one of those that takes different actions: they prefer to support Israel. The author aims to dissect the factors that make India support Israel. This is of course, related to decision-making carried out by a country, as explained by Richard Snyder. Decision-making is influenced by internal and external factors that show cause-and-effect relationships. Using descriptive-qualitative research methods, the author found several factors that made India prefer to support Israel. This form of support occurs because of the diplomatic relations the two countries have established to increase defense cooperation. India is doing this because the country is still overshadowed by the long-standing conflict that occurred due to mutual claims on the Kashmir border region with Pakistan. Besides that, India and Israel also collaborate in tourism and humanitarian matters, which are assessed using human environment indicators. All these factors show the rationality used by India in providing support to Israel.